DT5aP-Hib-IPV and MCC vaccines: preterm infants' response to accelerated immunisation. Issue 4 (21st March 2005) - Slack, M H; Cade, S; Schapira, D; Thwaites, R J; Crowley-Luke, A; Southern, J; Borrow, R; Miller, E
Abstract : Aims: To describe the immune response of preterm infants to combined diphtheria/tetanus/5 component acellular pertussis-Haemophilus influenzae type b inactivated polio vaccine (DT5aP-Hib-IPV) and meningococcal serogroup C conjugate vaccine (MCC) under accelerated schedule. To compare results with term infants immunised with DT5aP-Hib-IPV and with historical data from preterm infants immunised with a DT3 component aP-Hib vaccine. Methods: Prospective observational study in preterm infants born at <32 weeks gestation with comparison to contemporary cohort of term infants. DT5aP-Hib-IPV and MCC vaccines were given at 2, 3, and 4 months. Results: Fifty preterm infants (mean gestational age 28.5 weeks) completed the study. After three doses of vaccines Hib polysaccharide IgG geometric mean concentration (GMC) was 1.21 μg/ml with 80% ⩾0.15 μg/ml; MCC serum bactericidal assay geometric mean titre (GMT) was 1245 with 100% ⩾8. All infants achieved protective titres to diphtheria, tetanus, and the three poliovirus types with ⩾80% achieving protective rises in IgG against the five pertussis antigens. Conclusion: Preterm infants immunised with DT5aP-Hib-IPV and MCC vaccines show IgG responses to Hib and MCC greater than seen historically in both term and preterm infants with a DT3aP-Hib vaccine, and for pertussis antigens and poliovirus type 1 responses similar to that seen in term infants immunised with DT5aP-Hib-IPV. Responses to poliovirus types 2 and 3 are reduced, but all infants achieved protective titres.